PENGARUH KECERDASAN EMOSIONAL DAN ORGANIZATIONAL CITIZIENSHIP BEHAVIOUR (OCB) TERHADAP KINERJA KARYAWAN MUDA DI SURABAYA - Dwiningtyas, Cornelia Ratna; Iswati, Iswati (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to: 1) determine the effect of emotional intelligence on the performance of young employees; 2) determine the effect of organizational citizenship behavior on the performance of young employees; and 3) determine the effect of emotional intelligence and organizational citizenship behavior on the performance of young employees in the city of Surabaya. Because it seeks to uncover the effect of the independent variable on the dependent variable, the approach used is a quantitative approach. The sample of this research is young employees in the city of Surabaya as many as 106 respondents. Data were collected through questionnaire, which were then analyzed by T-test (partial), F-test (simultaneous), and R2-test (determination) through the IBM SPSS v 25 application. The results of this study indicate that: 1) emotional intelligence affects the performance of young employees in the city of Surabaya; 2) organizational citizenship behavior affects the performance of young employees in the city of Surabaya; and 3) emotional intelligence and organizational citizenship behavior affects the performance of young employees in the city of Surabaya. The ability of the two independent variables to affects employee performance variables simultaneously was 71.8%, with details of emotional intelligence contributed 43.2%, while organizational citizenship behavior contributed 28.6%.Keywords: Emotional Intelligence, Organizational Citizenship Behavior(OCB), Employee Performance, Young Employees.